Hospital-based seroepidemiological analysis of varicella antibodies in children without history of varicella disease - Zhang, Zhongyang; Chen, Zengsheng; Li, Xiaofan; Hu, Ping; Hao, Sicheng; Liu, Sitong; Yang, Feng (The Journal of Infection in Developing Countries, 2025)
Introduction: There are no published studies on the anti-varicella zoster virus (VZV) IgG antibody status of children in Qingdao. Thus, the aim of the present study was to investigate anti-VZV antibody status in hospital-based children aged 0–13 years without a history of varicella disease. Methodology: Children aged 0–13 years in Qingdao were included in the study population. The demographic data and vaccination histories of all the subjects were obtained from the Shandong Information System for Immunization Program. Varicella disease history data was obtained from the Chinese Information System for Disease Control and Prevention. Enzyme-linked immunosorbent assay was used for detecting anti-VZV IgG in serum samples, and the seropositivity rate and geometric mean concentration (GMC) of the antibody were analyzed. Results: A total of 983 children were included in the study. The seropositivity rate was 55.04%, and the GMC was 121.74 mIU/mL. The seropositivity rate and antibody GMC were significantly higher in females than in males (p < 0.05) and significantly higher in children aged 4–6 years than in children aged < 4 years and 7–13 years (p < 0.001). The seropositivity rate and GMC in children increased with vaccine dose (p < 0.001). In contrast to the considerable decline in antibody levels 3–5 years after one dose of varicella vaccination, antibody levels observed at least 8 years after two doses of varicella vaccination showed no considerable decline. Conclusions: Two-dose varicella vaccination is recommended for inclusion in China’s national immunization program.